Towards the electrochemical diagnosis of cancer: nanomaterial-based immunosensors and cytosensors. Issue 113 (25th November 2016) - Anik, Ülkü; Timur, Suna
Abstract : In this review, nanomaterial based electrochemical biosensors including electrochemical immunosensors and cytosensors towards cancer detection are covered. Abstract : In this review, nanomaterial based electrochemical biosensors including electrochemical immunosensors and cytosensors towards cancer detection are covered. Brief definitions of biosensors together with nanomaterials are presented. Electrochemical biosensors for cancer biomarkers and cytosensors are listed. Also, the potential of adaptation of these biosensors to point of care systems is discussed.